Clinical competency in child maltreatment for community nurses in Taiwan. (March 2015) - Chen, Yi‐Wen; Huang, Joh‐Jong; Lu, Tsung‐Hsueh; Feng, Jui‐Ying
Abstract : The purpose of this cross‐sectional study was to examine aspects of competency in child abuse among community nurses in Taiwan. A sample of 650 community nurses were recruited from public health centres (PHC) and outpatient clinics in Southern Taiwan. A structured questionnaire with five subscales, knowledge, skills, empowerment, team collaboration and self‐reflection was developed and used for data collection. A total of 588 questionnaires were returned and used for analysis. Nearly 20% of community nurses reported having an acquaintance with a maltreatment history. Only 4.6% had experience of reporting a case of child abuse. Most nurses reported strong skills and abilities (empowerment, team collaboration and self‐reflection). Outpatient clinic nurses scored higher in four subscales than the PHC nurses. Nurses who had a history as a victim or had reporting experience claimed better clinical competency. Unfortunately, community nurses had limited knowledge in child abuse. The findings support the development of continuing education programmes on child abuse for community nurses.